Construire l’école: de la planification à la privatisation, politiques publiques et architecture scolaire en Angleterre et au Pays de Galles depuis 1945 - Françoise Granoulhac (Revue LISA)
This article reviews sixty years of school building policies and educational development and studies the impact of these policies on school design. After a long period of central planning followed by years of crisis and neglect, the Labour government elected in 1997 opened up new directions, encouraging the development of the Private Finance Initiative. This article discusses the issues raised by increased private sector participation in school funding, design and management and examines the changing relationship between the main stakeholders: central government, local authorities and private organisations. Whilst privatisation and school autonomy are promoted, central control on the delivery of programmes is being strengthened. Finally, in spite of such drastic changes, it is argued that the architectural legacy of the post-war era still informs current design.